Assessment of knowledge and awareness of breast cancer among rural women in Telangana, South India - Pydipalli, Mounika; Roy, Pritam Kumar (International Journal Of Community Medicine And Public Health, 2021)
Breast cancer is the most common type of cancer diagnosed in women globally contributing around 15% of mortality. In India, it is the second most common cancer with the incidence in rural areas being twice than in urban. There is lack of knowledge and awareness of breast cancer especially in rural areas. So this survey was conducted to assess the existing levels of awareness to plan comprehensive health programs, early detection and carrying out treatment campaigns. A cross-sectional survey was carried out among the attendees of patients visiting cervical cancer screening centre in Mahbubnagar, Telangana from May 2020 to June 2020. A total of 60 participants were selected by convenient sampling. Data was collected using a pretested questionnaire. Out of a total of 60 participants, nearly two-third (63.3%) women had some knowledge regarding cancers and less than half were aware of breast cancer (45%). Among those who were aware (27), more than three-fourth did not know about symptoms of breast cancer (77.8%) and had not undergone any breast cancer screening (77.7%). It is necessary to increase community participation through social mobilization by engaging the human resources at the grass root level.